The Role of the Liver in the Pathophysiology of PCOS: A Literature Review - Abrar Alhermi; Heather Perks; Varsha Nigi; Noor Altahoo; Stephen L. Atkin; Alexandra E. Butler (Biomolecules)
Polycystic ovary syndrome (PCOS) is the most common endocrine metabolic disorder found in women of reproductive age and is characterized by both metabolic and reproductive dysfunction. Women with PCOS commonly have insulin resistance, increased susceptibility to type 2 diabetes mellitus, dyslipidemia, hyperinsulinemia, increased cardiovascular risk, hepatic steatosis, infertility, and an overall reduction in physical and psychological well-being. Several previous studies have shown a causal association between PCOS and hepatic disorders, such as chronic liver disease (CLD) and nonalcoholic fatty liver disease (NAFLD), where PCOS was identified as contributing to the hepatic features. Whilst it is recognized that PCOS may contribute to hepatic dysfunction, there is also evidence that the liver may contribute to the features of PCOS. The purpose of this review is to discuss the current understanding regarding hepatic involvement in PCOS pathophysiology, the inflammatory markers and hepatokines involved in the development of PCOS, and the role of genetics in the occurrence of PCOS. This review illustrates that PCOS and NAFLD are both common disorders and that there is both genetic and metabolic linkage between the disorders. As such, whilst PCOS may contribute to NAFLD development, the converse may also be the case, with a potential bidirectional relationship between PCOS and liver disease.